Expression of L1CAM, COX-2, EGFR, c-KIT and Her2/neu in anaplastic pancreatic cancer: putative therapeutic targets? - Bergmann, Frank; Moldenhauer, Gerhard; Herpel, Esther; Gaida, Matthias; Strobel, Oliver; Werner, Jens; Esposito, Irene; Sebens, Susanne; Schirmacher, Peter; Kern, Michael A. (Histopathology, 2010)
AIMS: Undifferentiated (anaplastic) pancreatic cancer and undifferentiated pancreatic carcinoma with osteoclast-like giant cells (giant cell tumour) are rare variants of pancreatic ductal adenocarcinoma. Representing biologically highly aggressive neoplasms, they are frequently diagnosed at an advanced stage. The response to established chemo- or radiochemotherapeutic treatment regimens is poor, and undifferentiated pancreatic cancer generally has a dismal prognosis. As additional therapeutic options have not yet been investigated in undifferentiated pancreatic cancer, the aim was to analyse the expression of putative therapeutic targets that have shown promising results in various other neoplasms. - METHODS AND RESULTS: Fifteen cases of undifferentiated pancreatic cancer (seven containing osteoclast-like giant cells) were investigated clinicopathologically and immunohistochemically for putative therapeutic targets. Whereas L1CAM, cyclooxygenase (COX)-2 and epidermal growth factor receptor (EGFR) were found to be significantly expressed in 80%, 93% and 87% of the investigated tumours, respectively, there was no substantial expression of c-kit (CD117) and there was no detectable expression of Her2/neu. - CONCLUSIONS: The expression of L1CAM, COX-2 and EGFR in the majority of undifferentiated pancreatic carcinomas suggests that they might represent targets for adjuvant therapy in anaplastic pancreatic cancer. On the other hand, c-kit and Her2/neu seem to have no relevance for the therapy of these tumours.